A new surgical technique for concealed penis using an advanced musculocutaneous scrotal flap - Han, Dong-Seok (BMC Urol, 2015)
BACKGROUND: Until recently, no single, universally accepted surgical method has existed for all types of concealed penis repairs. We describe a new surgical technique for repairing concealed penis by using an advanced musculocutaneous scrotal flap. METHODS: From January 2010 to June 2014, we evaluated 12 patients (12–40 years old) with concealed penises who were surgically treated with an advanced musculocutaneous scrotal flap technique after degloving through a ventral approach. All the patients were scheduled for regular follow-up at 6, 12, and 24 weeks postoperatively. The satisfaction grade for penile size, morphology, and voiding status were evaluated using a questionnaire preoperatively and at all of the follow-ups. Information regarding complications was obtained during the postoperative hospital stay and at all follow-ups. RESULTS: The patients’ satisfaction grades, which included the penile size, morphology, and voiding status, improved postoperatively compared to those preoperatively. All patients had penile lymphedema postoperatively; however, this disappeared within 6 weeks. There were no complications such as skin necrosis and contracture, voiding difficulty, or erectile dysfunction. CONCLUSIONS: Our advanced musculocutaneous scrotal flap technique for concealed penis repair is technically easy and safe. In addition, it provides a good cosmetic appearance, functional outcomes and excellent postoperative satisfaction grades. Lastly, it seems applicable in any type of concealed penis, including cases in which the ventral skin defect is difficult to cover.